A hora e o lugar das Ordens Sufis na tradição islâmica - Mateus Soares de Azevedo (Araucaria)
What is Sufism? In what does it believe? What are its main practices? Is it a mystical strand of Islam for a few, or a way open to many? What are the Sufi orders? What are their nature and reason for being? What are their origin and historical development? Are they “initiatic” and aimed at a spiritual elite, or are the Sufi Orders “popular” and accessible in principle to all believers? These are some of the questions that this essay seeks to answer.